OPTIMASI SISTEM PEMANFAATAN EKSKRETA AYAM PETELUR SEBAGAI BAHAN BAKU PEMBUATAN PELET PAKAN IKAN LELE - , TONI SUPOMO,S.T., Prof. Dr. Ir. Ali Agus, DAA., DEA. ([Yogyakarta] : Universitas Gadjah Mada, 2012)
Demand of fishfeed always increase year by year caused increasing of fish consumption. The price of fishfeed will be the point problem in fish conducting. In other hand, there are many chicken livestock which produce solid waste in the form of excreta laying hens or manure that contains many protein and fat. Excreta laying hens tries exploited to be made fishfeed in the form of pellet for Clarias sp. The aim of this research is to know that excreta laying hens or manure could be made as raw material of fish pellet, by doing formulation with Pearsons Square method at various formulas FR1, FR2, FR3, and FR4. Fish pellet is printed with pelletizer 0,5 HP. Then proximate test was done to know fat and protein contains appropriate SNI, also quality of physical test for pellets and acceptability test for Clarias sp. Based on proximate test, the formulas that appropriate SNI in protein contains are FR3 and FR4 that contains 25,02% and 25,21%, with minimum protein standard of 25%. The fat content fulfilling SNI are FR3 and FR4 that contains 5,52% and 5,76% with minimum standard of 5%. For quality of physical test, all of formula fulfilled the standard. The result of acceptability test is FR3 well accepted by Clarias sp. with significant value 0,694-0,977 to conventional fishfeed. The feasibility study for small and medium enterprise of fishfeed from excreta laying hens with 110 kg/day capacities yields value BCR 1,20, BEP 83,47 % capacity, ROI 25,08 %, and PBP during 8 months.